INOVASI DALAM PELAYANAN PUBLIK DI DESA MONTONG GAMANG KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH - Lalu Budiman (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the influence of technology-based innovation on bureaucratic effectiveness in Montong Gamang Village, Kopang District, Central Lombok Regency. The method used is descriptive qualitative with a case study approach. Data were obtained through in-depth interviews, observations, and document analysis. The results show that technological innovations, such as the Village Information System (SID) and online service applications, improve the efficiency, transparency, and accountability of public services. Despite their positive impact, the implementation of innovations faces obstacles such as limited infrastructure, low digital literacy, and resistance to change. This study recommends strengthening infrastructure, ongoing training, and increasing community involvement to support the absence of innovation. These findings contribute to the development of literature related to public service innovation at the village level.